2020
DOI: 10.1002/acn3.51063
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic conditioning combined with intravenous thrombolysis for acute ischemic stroke

Abstract: ObjectiveThe objective of this study was to investigate the safety and efficacy of remote ischemic conditioning (RIC) combined with intravenous thrombolysis (IVT) in the treatment of acute ischemic stroke (AIS).MethodsPatients with AIS who underwent IVT were enrolled and 1:1 randomized to the RIC group and sham‐RIC group in this study. RIC (or sham‐RIC) was performed twice within 6–24 h of IVT. The subjects in the two groups were followed up for 90 days. The safety outcome included the ratio of hemorrhagic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 22 publications
2
36
0
1
Order By: Relevance
“…None of the human trials succeeded in applying the intended RIC protocol; trials had low completion rates that were not taken into account in the data analysis and interpretation of results 32,33,37,38 . A recent study published following the completion of our final search reported to complete all intended cycles but reported no clinical effect of RIC 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the human trials succeeded in applying the intended RIC protocol; trials had low completion rates that were not taken into account in the data analysis and interpretation of results 32,33,37,38 . A recent study published following the completion of our final search reported to complete all intended cycles but reported no clinical effect of RIC 44 …”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 , 37 , 38 A recent study published following the completion of our final search reported to complete all intended cycles but reported no clinical effect of RIC. 44 …”
Section: Discussionmentioning
confidence: 99%
“…With respect to platelet function and the coagulation cascade, animal models have demonstrated the fibrinolytic and anticoagulant benefits of RIC [ 97 ]. However, this benefit has not been observed in humans [ 41 , 46 , 52 , 116 ]. Following the ERIC-PPCI/CONDI-2 trial, a subsequent sub-analysis of the study population was performed to look for fibrinolysis benefit, but no firm trends were observed, with the exception of a reduction in time to thrombosis at 48 h [ 41 ].…”
Section: Does Ric Mediate Innate Immune Cell Activity?mentioning
confidence: 99%
“…27 The primary aims for many of these studies are to establish whether RIPerC and/or early RIPostC is safe and can reduce stroke severity assessed by clinical and radiological indicators. Alongside this, several studies are investigating the feasibility of hyperacute RIC alongside intravenous thrombolysis (SERICT-AIS -NCT04027621 28 ; rTPA-RIC -NCT02886390; rTPA-RIC1 -NCT03231384; TRIPCAIS -NCT03218293) and ET (PROTECT-I -NCT03915782; REVISE-2 -NCT03045055; RICE-PAC -NCT03152799). While the most trials are investigating whether RIC in ischaemic stroke, a subset of studies are investigating RIC in intracerebral haemorrhage and subarachnoid haemorrhage (online supplemental material).…”
Section: Riperc and Early Ripostcmentioning
confidence: 99%